(untitled) (Advancements in Homeopathic Research, 2023)
Polycystic ovarian syndrome (PCOS) is one of the most common hormonal disorders among women of reproductive age and a leading cause of female infertility. A case successfully treated by homoeopathy is presented here to acquaint the homoeopathic physicians about the efficacy of homoeopathic medicine selected on individualistic basis in the treatment of PCOS.